(untitled) (Our Nature, 2018)
Global climate change is a major problem generated by increasing concentration of carbon dioxide in the atmosphere. Forests and their soils are major sink of carbon and thus constitute an effective role in the global carbon cycle. Present study was conducted to quantify and compare the amount of carbon stock in litterfall, fine root and soil between Tarai Sal forest and Hill Sal forest of eastern Nepal. Carbon stock in litter and fine root was estimated by ash content method and in soil by multiplying the value of soil organic carbon, bulk density and soil depth. Carbon stock in litterfall was higher (3.94 Mg ha-1) in TSF than HSF (3.26 Mg ha-1) and in fine root (0-5 mm size) in 0-30 cm soil depth it was higher in HSF (2.76 Mg ha-1) than TSF (2.19 Mg ha-1). In soil (0-30 cm depth) the value was higher in HSF (58.23 Mg ha-1) than TSF (50.81Mg ha-1). Tarai Sal forest accumulated higher carbon stock in the litterfall and lower in fine root than Hill Sal forest which was mainly attributed to the amount of litterfall and fine root biomass rather than organic carbon concentration. In Tarai Sal forest the carbon stock in soil was relatively low than Hill Sal forest that may be due to the higher net uptake and mineralization of carbon in the situation of higher growth rate of plant. These outcomes verified that the forest plays important role for mitigation of global warming by storing the atmospheric carbon dioxide in plant parts and the soil. So, it concludes that conserving the considerable quantity of carbon in forests is inevitable for proper forest management.